The Influence of Human Resources, Communications Information Technology (ICT), and Leadership on The Quality of Passport Issuance Public Services in Manokwari Class I Non-TPI Immigration Offices - Nurliana, Dian Pratiwi Agustina; Hafel, Muhlis; Herningsih, Herningsih (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Based on the results of research, analysis, and discussion of case studies at the Class I Non-TPI Manokwari Immigration Office, it is concluded that the influence of Human Resources, Information Communication Technology, and Leadership on the Quality of Passport Issuance Services at the Office is very significant. Human Resources have a big impact on service quality, as evidenced by the high significance value (t = 4.991, p < 0.05) and the indicator